Broodmaaltijd op de eerste congresdag. Zittend v.l.n.r. Jacobsen, ?, van der Pijll, ?, Lindeman. Staand 3e van links Regter
Broodmaaltijd op de eerste congresdag. Zittend v.l.n.r. Jacobsen, ?, van der Pijll, ?, Lindeman. Staand 3e van links Regter.